Новый вид рода Dendrolaelaspis (Gamasina, Rhodacaridae) с Украины - Щербак, Г.И.; Скляр, В.Е. (Вестник зоологии, 1983)
Dendrolaelaspis poltavae sp. n., similar to D. lindquisti, differs by longer Dy, chetal topography of the hind half of notogaster and by the shape of My. Female, male and deutonymph of the new species are described and depicted. Type-locality: Ukrainian SSR, Poltava environs, under bark of a Populus tree. In adults D₇; (2XD₅), M₈ (3XD₅), S₆ (2XD₅), M₉ (1.5XD₅), Pl₄ and Pl₅ (1.5XD₅) bear on ips thin transparent spearshaped spreadings, Dy — short spine-shaped, M₁₀ (5XD₅) — thick flagelliform. The shape and topography of these chetae in deutonymphs are considerably different from those in adults (Fig. 3 a, 6). Length of the female ventro-anal shield exceeds its width, the shield bears six pairs of chetae, behind shield Vi and the longest on ventral side with Spread soft tips Vs